2021
DOI: 10.1007/s00784-021-04112-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial translocation and microgap formation at a novel conical indexed implant abutment system for single crowns

Abstract: Objectives A conometric concept was recently introduced in which conical implant abutments hold the matching crown copings by friction alone, eliminating the need for cement or screws. The aim of this in vitro study was to assess the presence of microgap formation and bacterial leakage at the Acuris conometric restorative interface of three different implant abutment systems. Material and methods A total of 75 Acuris samples of three implant-abutment syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It was demonstrated through in vitro microbiological testing that there is no presence of bacteria either living or dead in the portions inside the prosthetic conometric connection. This can, therefore, be considered an acceptable prosthetic component from this point of view [6,26]. Scanning electron microscope (SEM) analysis of the marginal area showed minute and punctual micro-gaps (1.67-2.04 µm), although planar surfaces were in intimate contact [26].…”
Section: Marginal Adaptation and Bacterial Sealingmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated through in vitro microbiological testing that there is no presence of bacteria either living or dead in the portions inside the prosthetic conometric connection. This can, therefore, be considered an acceptable prosthetic component from this point of view [6,26]. Scanning electron microscope (SEM) analysis of the marginal area showed minute and punctual micro-gaps (1.67-2.04 µm), although planar surfaces were in intimate contact [26].…”
Section: Marginal Adaptation and Bacterial Sealingmentioning
confidence: 99%
“…This can, therefore, be considered an acceptable prosthetic component from this point of view [6,26]. Scanning electron microscope (SEM) analysis of the marginal area showed minute and punctual micro-gaps (1.67-2.04 µm), although planar surfaces were in intimate contact [26]. The average gaps between the conometric connection of the analyzed systems vary between 2 and 3 µm; considerably greater is the discrepancy between the hood and the prosthetic crown, which has a gap that can reach up to 145 µm: this is a virtual gap; in fact, with the cementation procedures, the latter is filled [26].…”
Section: Marginal Adaptation and Bacterial Sealingmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Micro gaps and micromotion at the connection between the abutment and the implant are common problems in two-stage systems and may lead to local inflammation and bone loss. 19,20 Studies have suggested that the platform switch technique can help prevent marginal bone loss (MBL) around the implants. [21][22][23][24][25][26][27] The balanced base abutment is a commonly used component in the Ankylos implant system for edentulous patients.…”
Section: Introductionmentioning
confidence: 99%
“…The abutment is an important component of the implant system, and the design of abutment affects the soft and hard tissue around the implant 17,18 . Micro gaps and micromotion at the connection between the abutment and the implant are common problems in two‐stage systems and may lead to local inflammation and bone loss 19,20 . Studies have suggested that the platform switch technique can help prevent marginal bone loss (MBL) around the implants 21–27 .…”
Section: Introductionmentioning
confidence: 99%